The landscape of different molecular modules in an immune microenvironment during tuberculosis infection. Issue 5 (31st March 2021) - Zhang, Nan; Luo, Xizi; Huang, JuanJuan; Song, Hongyan; Zhang, Xinyue; Huang, Honglan; Zhao, Shishun; Wang, Guoqing
Abstract: Tuberculosis is a chronic inflammatory disease caused by Mycobacterium tuberculosis . When tuberculosis invades the human body, innate immunity is the first line of defense. However, how the innate immune microenvironment responds remains unclear. In this research, we studied the function of each type of cell and explained the principle of an immune microenvironment. Based on the differences in the innate immune microenvironment, we modularized the analysis of the response of five immune cells and two structural cells. The results showed that in the innate immune stress response, the genes CXCL3, PTGS2 and TNFAIP6 regulated by the nuclear factor kappa B(NK-KB) pathway played a crucial role in fighting against tuberculosis. Based on the active pathway algorithm, each immune cell showed metabolic heterogeneity. Besides, after tuberculosis infection, structural cells showed a chemotactic immunity effect based on the co-expression immunoregulatory module.